Glucocorticoid and cAMP induction mechanisms are differentially affected by the p85gag-mos oncoprotein. - Hamilton, B J (1989)
The inability to perceive and coordinate both internal and external signals that function to regulate cellular growth and proliferation is a hallmark of oncogenic transformation. To examine the effects of the v-mos oncogene on distinct signal transduction pathways, the 6m2 cell line was used, in which expression of the p85gag-mos oncogene, and consequently transformation, are temperature sensitive. Through the analysis of endogenous metallothionein 1 (Mt-1) gene expression in 6m2 cells, p85gag-mos effects on glucocorticoid, cAMP, and heavy-metal induction were examined. While heavy-metal induction of Mt-1 mRNA was found to be unaffected by p85gag-mos, differential effects were exerted upon glucocorticoid and cAMP induction of Mt-1. Glucocorticoid induction of Mt-1 mRNA in p85gag-mos-transformed 6m2 cells was initiated normally but not maintained to the same extent as in nontransformed 6m2 cells. In contrast, cAMP did not induce Mt-1 mRNA in p85gag-mos-transformed 6m2 cells, although a significant induction was noted in nontransformed 6m2 cells. Thus, an oncoprotein interferes with different steps in each particular signal transduction pathway, ultimately causing abnormalities of inducible gene expression.